Nauczanie responsywne – nowe pojęcie w nauczaniu - Szymiec, Robert (Wydawnictwo Naukowe UAM w Poznaniu, 2011)
Artykuł prezentuje nową koncepcję nauczania responsywnego, jako zerwanie z tradycyjnym modelem nauczania opartego na programach nauczania. W nowym modelu edukacji przerabianie programu ma być zastąpione przez podążanie za naturalną ciekawością ucznia i chęcią poznawania świata, realizowaną poprzez media elektroniczne. Zasoby edukacji zdalnej i jej najefektywniejsze metody mają zastąpić podręczniki szkolne, używając między innymi intensywnej eksploracji Internetu, jak również specjalnych platform internetowych, takich jak „SuperMemo”.

The article introduces a new concept of responsive teaching, as breaking away from traditional program- based teaching. This traditional model is to be replaced by education following the natural student’s curiosity and the desire for world exploration, by using electronic media. The teacher becomes a follower of student’s interests, or a facilitator of such exploration with a friendly attitude. The newest and most powerful distant learning methods and technologies are to replace traditional coursebooks.These include intensive Internet exploration and interaction, as well as working on specific platforms like “SuperMemo” providing distant teacher insight of every student working input and intensive use of social platforms
The responsive teaching – a new concept of education
Keywords: Nauczanie responsywne; Responsive teaching; Kształcenie zdalne; Distant learning